Assimilation efficiencies and elimination rates of silver, cadmium and zinc accumulated by trophic pathway in Gammarus fossarum - Gestin, Ophélia; Lopes, Christelle; Delorme, Nicolas; Garnero, Laura; Geffard, Olivier; Lacoue-Labarthe, Thomas (Peer Community Journal)

(untitled)
To improve the assessment of metal toxicity in aquatic organisms, it is important to consider the different uptake pathways (i.e. trophic or aqueous). The bioaccumulation of dissolved metals such as Cd and Zn in gammarids is beginning to be well described. However, there are very few data on the contribution of the dietary pathway, and its associated toxicokinetic parameters. Among these, the assimilation efficiency (AE) is an essential parameter for the implementation of models that take the trophic pathway into account. This study aims to estimate the assimilation efficiencies and elimination rates of two types of food, i.e. alder leaves and chironomid larvae, contaminated with three metals (Ag, Cd and Zn) of major concern for the Water Framework Directive (WFD). The pulse-chase-feeding method was used. Gammarids were fed with alder leaves or chironomid larvae previously contaminated with 110mAg, 109Cd or 65Zn, for a short period of time (1 to 5 hours), followed by an elimination phase of 14 days. At different time points, the gammarids were placed alive on the gamma detector to individually quantify whole body concentrations of 110mAg, 109Cd or 65Zn. Our results indicate that: i) Cd has the highest assimilation efficiency (39% for leaves and 19% for larvae), followed by Zn (15% for leaves and 9% for larvae) and Ag (5% for leaves); ii) for Cd and Zn, the AE were higher when gammarids were fed with leaves than with larvae; iii) the elimination rates of metals seem to depend more on the food matrix than on the metal assimilated; and thus iv) the biological half-life calculated from the kes is 5.1 days for Ag, between 4.9 and 13 days for Cd and between 3.8 and 13 days for Zn.